(3aYGdjI GSJNOGe GdCdYGH GdJQHhjI aj JfejI GdegGQGJ GdMQcjI GdGSGSjI dOi CWaGd eGbHd GdeOQSI (B( 4 - 5 (3SfhGJ(B) s - (3CejQ, LejdIs; (3eQGRbI, LeGds; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2024)
(3Edi GdJYQa Ydi aYGdjI GSJNOGe GdCdYGH GdJQHhjI hOhQgG aj JfejI GdegGQGJ GdMQcjI GdCSGSjI (B)(3GdegGQGJ GdMQcjI GdGfJbGdjI, egGQGJ GdJMce hGdSjWQI, egGQGJ GdKHGJ hGJRGf GdLSe(B) (3dOi CWaGd eQMdI eG bHd GdeOQSI HYeQ(B(4-5) (3SfhGJ, hef CLd JMbjb GdgOa SYi GdHMK ddJMbb ef GdaQVjGJ GdJGdjI(B: - (3JhLO aQhb PGJ OdGdI EMUGFjI YfO eSJhi GdOdGdI (B0.05 (3Hjf CWaGd GdeLehYI GdJLQjHjI hGdVGHWI aj JfejI HYV GdegGQGJ GdMQcjI GdGfJbGdjI aj GdbjGS GdHYOj hdUGdM GdeLehYI GdJLQjHjI(B. - (3JhLO aQhb PGJ OdGdI EMUGFjI YfO eSJhi GdOdGdI (B0.05 (3Hjf CWaGd GdeLehYI GdJLQjHjI h GdVGHWI aj JfejI HYV egGQGJ GdJMce hGdSjWQI aj GdbjGS GdHYOj hdUGdM GdeLehYI GdJLQjHjI(B. - (3JhLO aQhb PGJ OdGdI EMUGFjI YfO eSJhi GdOdGdI (B0.05 (3Hjf CWaGd GdeLehYI GdJLQjHjI h GdVGHWI aj JfejI HYV egGQGJ GdKHGJ hGJRGf GdLSe aj GdbjGS GdHYOj hdUGdM GdeLehYI GdJLQjHjI(B. (3hdJMbjb CgOGa GdHMK GSJNOeJ GdHGMKI GdefgL GdJLQjHj, GdbGFe Ydi JUeje GdeLehYJjf GdJLQjHjI hGdVGHWI, hUeeJ hSGFd hCOhGJ HMKjI dJMbjb Pdc hJeKdJ Ydi GdBJj(B: - (3GdHQfGeL GdebJQM(B. - (3GNJHGQGJ GdegGQGJ GdMQcjI GdCSGSjI(B. (3hHYO eG JCcOJ GdHGMKI ef UOb hKHGJ COhGJ GdHMK, JeJ GdOQGSI GdejOGfjI GdJLQjHjI Ydi eSJhi GdQhVGJ GdNGUI dhdGjI JjRj hRh (B)(3HdOjI aQjMI(B((3, hJe ENJjGQ YjfI GdHMK HWQjbI bUOjI, hgPG fXQG deG JJhaQ Ydjg ef EecGfjGJ hhSGFd GddGReI dJWHjb GdHQfGeL GdebJQM, hTed GdHMK Ydi YjfI ef GdCWaGd hGdPj HdZ YOOge (B(60) (3Wad, MjK (B(30) (3efge jeKdhf GdeLehYI GdVGHWI hGdPjf jNVYhf dHQfGeL GdQhVI GdYGOj, h(B(30) (3Wad jeKdhf GdeLehYI GdJLQjHjI hGdJj Sha jWHb YdjgG GdHQfGeL GdebJQM ef WQa GdHGMKI(B. (3hbO GSJNOeJ GdHGMKI YOOG ef GdCSGdjH GdEMUGFjI ddhUhd Edi fJGFL GdHMK hefgG MSGH bje(BT) ) (3GdeMShHI dJMOjO OdGdI GdaQhb Hjf GdeLehYJjf GdJLQjHjI hGdVGHWI aj GdGNJHGQGJ GdbHdjI hGdHYOjI ajeG jNU JfejI GdegGQGJ GdMQcjI GdCSGSjI hgPG HGSJNOGe HQfGeL (BSPSS (3EUOGQ(B23 (3, hHYO JMdjd hefGbTI GdfJGFL CSaQJ Ydi eG jdj(B: - (3hLhO aQhb PGJ OdGdI EMUGFjI YfO eSJhi GdOdGdI (B0.05 (3Hjf CWaGd GdeLehYI GdJLQjHjI hGdeLehYI GdVGHWI aj JfejI HYV GdegGQGJ GdMQcjI GdGfJbGdjI aj GdbjGS GdHYOj dUGdM GdeLehYI GdJLQjHjI(B. - (3hLhO aQhb PGJ OdGdI EMUGFjI YfO eSJhi GdOdGdI (B0.05 (3Hjf CWaGd GdeLehYI GdJLQjHjI hGdeLehYI GdVGHWI aj JfejI HYV egGQGJ GdJMce hGdSjWQI aj GdbjGS GdHYOj dUGdM GdeLehYI GdJLQjHjI(B. - (3hLhO aQhb PGJ OdGdI EMUGFjI YfO eSJhi GdOdGdI (B0.05 (3Hjf CWaGd GdeLehYI GdJLQjHjI hGdeLehYI GdVGHWI aj JfejI HYV egGQGJ GdKHGJ hGJRGf GdLSe aj GdbjGS GdHYOj dUGdM GdeLehYI GdJLQjHjI(B. (3Ef GdfJGFL GdJj Bd EdjgG GdHMK LGAJ aj UGdM GdeLehYI GdJLQjHjI GdJj GSJNOeJ GdCdYGH GdJQHhjI, eeG jDcO aGYdjI GdHQfGeL GdebJQM HGSJNOGe GdCdYGH GdJQHhjI aj feh HYV ef GdegGQGJ GdMQcjI GdCSGSjI (B)(3GdegGQGJ GdMQcjI GdGfJbGdjI, egGQGJ GdJMce hGdSjWQI, egGQGJ GdKHGJ hEJRGf GdLSe(B). s
(3OcJhQGIs
Keywords: (3GdGdYGH GdJQHhjIs; (3GdQhVIs; (3GdegGQGJ GdMQcjIs; (3GdfTGW GdHOfj GdQjGVj eG bHd GdeOQSjs; (3Yde GdMQcIs